PENGARUH PENGETAHUAN, SIKAP, RIWAYAT KONTAK DAN KONDISI RUMAH TERHADAP KEJADIAN TB PARU DI WILAYAH KERJA UPTD PUSKESMAS HUTARAKYAT KABUPATEN DAIRI TAHUN 2019 - INTAN NOBERTA SIGALINGGING; WISNU HIDAYAT; FRIDA LINA TARIGAN (JURNAL ILMIAH SIMANTEK, 2019)
Tuberculosis is an infectious disease caused by TB germs where most TB attacks the lungs but can also attack other parts.The purpose of this study was to analyze the effect of knowledge, attitudes, contact history and home conditions on the incidence of pulmonary TB in the work area of the Hutarakyat District Health Center UPTD in 2019.Tuberculosis is an infectious disease caused by TB bacteria (Mycobacterium Tuberculosis) where most TB attacks the lungs but can also attack other parts.The type of this research is analytic correlation research with cross sectional method. The population in this study was 150 people suspected of suspected / suspected pulmonary tuberculosis and 60 pulmonary TB patients, bringing a total population of 210 and a sample of 68 respondents. Analysis of the data used in this study consisted of univariate, bivariate and multivariate analysis. The results of the study were obtained:there is influence of knowledge(p=0,000; OR = 8,631), attitudes(p=0,000; OR = 12,444), contact history (p=0,000; OR = 26,400)and home conditions (p=0,000; OR = 8,861)on the incidence of pulmonary TB, the dominant factor influencing the incidence of pulmonary TB is attitude(p=0,007; OR = 26,400).From the results of the research obtained it is recommended to sufferers and suspected lung TB to maintain health through a healthy lifestyle and avoid various contacts with the surrounding environment so as not to transmit pulmonary TB and adhere to doctor's recommendations.